1980
DOI: 10.2135/cropsci1980.0011183x002000060010x
|View full text |Cite
|
Sign up to set email alerts
|

Major Gene Control of Nitrate Reductase Activity in Common Wheat1

Abstract: Two high‐yielding, short‐statured spring wheats (Triticum aestivum L.), ‘Anza’ and ‘UC 44‐111,’ differ in certain characteristics of N metabolism. Nitrate reductase activity (NRA), measured in vitro on shoots or lamina of seedling plants, was about 8 and 18 µmoles of nitriteproduced/hour/g fresh weight for Anza and UC 44‐111, respectively. The genetic basis for this difference was investigated with an in vitro NRA assay on seedling plants to determine the NRA frequency distributions of parents, F1, F2, recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Our results confirmed the finding of Rao et al, (1977) and Gallagher et al, (1980) that UC 44-111 wheat was significantly higher in NR activity than Anza. This genotypic difference persisted in both the presence and absence of varying degrees of Al stress imposed in nutrient solutions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirmed the finding of Rao et al, (1977) and Gallagher et al, (1980) that UC 44-111 wheat was significantly higher in NR activity than Anza. This genotypic difference persisted in both the presence and absence of varying degrees of Al stress imposed in nutrient solutions.…”
Section: Discussionsupporting
confidence: 92%
“…Table 7 shows the effects of Al on the nitrate reductase activities during the second NO^-induced cycle (See Materials and Methods). Results confirmed the findings of Rao et al, (1977) and Gallagher et al, (1980) that ÜC 44-111 is higher in NR activity than Anza. They also showed that the NR activities are much higher in tops than in roots and that the NR activities of Anza tops were severely decreased by Al, but those of UC 44-111 tops were not.…”
Section: Downloaded By [] At 21:31 25 December 2014supporting
confidence: 88%
See 2 more Smart Citations
“…It is also observed that Al toxicity is closely related to nitrogen metabolism [92]. It was noted that nitrate reductase activity was higher in Al tolerant cultivars, when grown in Al treated nutrient solution [93]. Al interfered with the binding of the cations in the cell wall by the same order of magnitude as their respective influxes whereas phosphate binding was strongly enhanced [94].…”
Section: Nutritional Imbalancementioning
confidence: 99%